Staphylococcal enterotoxin A and toxic shock syndrome toxin compete with CD4 for human major histocompatibility complex class II binding. - Bavari, S (1995)
We have examined the role of the CD4 molecule in primary T-lymphocyte responses to the staphylococcal enterotoxins SEA, SEB, SEC1, and the toxic shock syndrome toxin TSST-1. Proliferating cells were predominantly CD4+; however, the responses to SEA and TSST-1 were most sensitive to inhibition by the anti-CD4 antibody Leu-3a. T-lymphocyte responses to the bacterial superantigens were inhibited by site-directed mutations of residues in the DR beta membrane-proximal domain (DR beta 2) that are also known to be important for interactions with CD4. SEA and TSST-1 binding to DR was reduced by the DR beta 2 mutations and by competition with soluble recombinant CD4. We propose that bacterial superantigens sequentially, or simultaneously with CD4, stabilize complexes of T-cell antigen receptors and major histocompatibility complex class II molecules. The superantigen qualities of these toxins may be due, in part, to a molecular mimicry of CD4 and other adhesion molecules.